Motivation in Extracurricular Volleyball Activities at State Senior High School in Pagar Alam - Alvin Anggara; Fitri Agung Nanda; Syamsuramel (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Extracurricular activities are educational activities outside of standard curriculum hours that aim to develop students' talents, interests, potential and character. .This research aims to determine the level of interest and motivation of students in participating in extracurricular volleyball activities at   Senior High School 4 Pagar Alam and to analyze the influencing factors. The type of research used is survey research with a quantitative descriptive approach. The research subjects were 22 students who actively participated in volleyball extracurricular activities. The research instruments include questionnaires, interviews, documentation and use the CIPP (Context, Input, Process, Product) model to assess various aspects of activity implementation. The research results show that students' interest and motivation are in the high category, with an average percentage of 77.67%. Judging from gender, male students have interest and motivation of 80.05%, while female students have 75.29%. Context obtained a score of 82.24% (very high), Input 71.10% (high), Process 77.14% (high), and Product 79.70% (high). These results show that volleyball extracurricular activities at  Senior High School 4 Pagar Alam run effectively, have a positive impact on improving skills, discipline, cooperation, and foster a sense of responsibility as students. It is hoped that this research can become a reference for schools to develop more interesting and productive extracurricular programs.